Prevalence and Associated Factors of Anemia Among Hospital Admitted Patients in Eastern Ethiopia - Yusuf MU; Abdurahman N; Asmerom H; Atsbaha T; Alemu A; Weldegebreal F (Journal of Blood Medicine, 2023)
Mohammed Umer Yusuf,1 Nuredin Abdurahman,1 Haftu Asmerom,2 Tesfaye Atsbaha,1 Adisu Alemu,3 Fitsum Weldegebreal2 1Department of Internal Medicine, School of Medicine, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2School of Medical Laboratory Sciences, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Pathology, School of Medicine, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Haftu Asmerom, School of Medical Laboratory Sciences, College of Health and Medical Sciences, Haramaya University, PO BOX 235, Harar, Ethiopia, Tel +251910089878, Email wawhaftu12@gmail.comBackground: Anemia is one of the most common comorbidities frequently seen in admitted patients. However, there is a scarcity of evidence regarding anemia among hospital admitted patients in Ethiopia, particularly in the Harari Region. Therefore, this study aimed to assess the prevalence and associated factors of anemia among hospital admitted patients in Eastern Ethiopia.Methods: A hospital-based cross-sectional study was conducted from October 25 to December 30, 2022. Four milliliters of venous blood were collected and complete blood count was done using the DxH 800 (Beckman Coulter, Inc, Miami, FL) hematology analyzer. The data were entered in Epi-data version 4 and exported to SPSS version 26 for statistical analysis. Bivariable and multivariable logistic regression models were fitted. The level of significance was declared at a p-value of < 0.05.Results: Of the 381 hospital admitted patients, 64.8% (95% CI = 60.01, 69.65) of the participants were anemic. Admitted patients who drank standard alcohol daily (AOR = 3.78, 95% CI = 1.71, 8.30), underweight (AOR = 9.39, 95% CI = 2.90, 30.46), and undernourished patients (AOR = 2.59, 95% CI = 1.15, 5.84), patients admitted with chronic kidney disease (AOR = 11.16, 95% CI = 4.06, 30.64), chronic liver disease (AOR = 3.20, 95% CI = 1.21, 8.47), deep vein thrombosis (AOR = 6.22, 95% CI = 1.98, 19.52), infectious disease (AOR = 9.71, 95% CI = 2.77, 34.02), and chronic non-communicable disease (AOR = 7.01, 95% CI = 1.90, 25.99) were all significantly associated with anemia.Conclusion: Anemia was common among hospital admitted patients and should prompt the focus on admission diagnoses that are likely to play leading roles in etiology. This information indicates a need for routine screening of anemia for all admitted patients to improve their health.Keywords: anemia, prevalence, associated factors, admitted patients, Ethiopia